2015
DOI: 10.1039/c4cy00673a
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically separable core–shell iron oxide@nickel nanoparticles as high-performance recyclable catalysts for chemoselective reduction of nitroaromatics

Abstract: A magnetically separable core–shell iron oxide@nickel nanocatalyst was synthesized, characterized and applied for the aromatic nitro group reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 62 publications
1
30
0
Order By: Relevance
“…Noble‐metal‐assisted reductions have been demonstrated involving Pd, Pt, Ag, and Au catalysts, with the use of H 2 gas as the cocatalyst. Nevertheless, the necessity of high H 2 gas pressures reduces recyclability and the high temperatures required present some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Noble‐metal‐assisted reductions have been demonstrated involving Pd, Pt, Ag, and Au catalysts, with the use of H 2 gas as the cocatalyst. Nevertheless, the necessity of high H 2 gas pressures reduces recyclability and the high temperatures required present some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Always there is a need for simplified method to produce catalyst, enhanced catalytic activity, recyclability of the heterogeneous catalyst, and versatility to use for various reactions. Many literatures indicated that the nanoparticle as catalysts can be easily separated and recycled with retention of catalytic activity compared to their bulk counterparts . In the past years, many hierarchical nanostructures have been used in catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxides containing iron as the main component are called ferrites with general formula MFe 2 O 4 (M = Co, Ni, Cu, etc.) . Ferrites are important magnetic materials with high magnetic character, low cost of production, high thermal and chemical stability, and a wide range of applications in scientific and industrial fields such as in transformer cores, permanent magnets, radio wave circuits, magnetic resonance imaging, high‐quality filters, antenna rods, magnetic recording media, operating devices, magnetic resonance amplifiers, etc .…”
Section: Introductionmentioning
confidence: 99%
“…These materials are broadly studied due to their electric, magnetic, catalytic and structural properties . When spinel ferrites are in the nanometric size range, they display superparamagnetic nature, which is of great interest due from the point of view of their application . Further, in a catalytic system, they can be easily separated from reaction media using an external magnet .…”
Section: Introductionmentioning
confidence: 99%